Naloxone fill rates after opioid overdose - Allison L Ruff; Kristian Seiler; Patrick Brady; A Mark Fendrick (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2019)
Over the past 25 years there has been a signifi cant increase in the use and misuse of opioid analgesic medications. In April 2018, the US Surgeon General released an advisory pressing more laypersons to become trained and get access to naloxone for emergency overdose situations. Utilizing the Clinformatics® Data-Mart Database of a large, national US health insurer, we assessed the rate of filling a naloxone prescription by individuals who have been seen or admitted for an opioid overdose. The rate of naloxone fi lls was extremely low, <1.0%, even for those patients who presented with more than one overdose episode. These fi ndings demonstrate the need for the rapid development and implementation of patient and prescriber-facing programs to increase the delivery of naloxone to those individuals most likely to benefi t from its use.